2019
DOI: 10.3389/fmars.2019.00404
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Science to Enhance Coastal Resilience and Adaptation

Abstract: Impacts from natural and anthropogenic coastal hazards are substantial and increasing significantly with climate change. Coasts and coastal communities are increasingly at risk. In addition to short-term events, long-term changes, including rising sea levels, increasing storm intensity, and consequent severe compound flooding events are degrading coastal ecosystems and threatening coastal dwellers. Consequently, people living near the coast require environmental intelligence in the form of reliable shortterm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 59 publications
0
14
0
1
Order By: Relevance
“…In terms of frameworks, we need to ensure that there are mechanisms and procedures to incorporate local knowledge to assist with risk assessments. For example, whilst many coastlines may share similar physical exposure from rise in sea levels and storm surge, different coastal communities have locally and regionally specific vulnerabilities, which requires substantial input from local community and decision makers to ensure that meaningful information is fed into observational and modelling programs used to address short‐ and long‐term risks (Nichols et al, ).…”
Section: Risk and Risk Elements As Defined By The Ipccmentioning
confidence: 99%
“…In terms of frameworks, we need to ensure that there are mechanisms and procedures to incorporate local knowledge to assist with risk assessments. For example, whilst many coastlines may share similar physical exposure from rise in sea levels and storm surge, different coastal communities have locally and regionally specific vulnerabilities, which requires substantial input from local community and decision makers to ensure that meaningful information is fed into observational and modelling programs used to address short‐ and long‐term risks (Nichols et al, ).…”
Section: Risk and Risk Elements As Defined By The Ipccmentioning
confidence: 99%
“…Parmi ce foisonnement d'usages de la notion de vulnérabilité, nous proposons une approche de ce que nous appelons la « vulnérabilité systémique » aux risques côtiers de submersion-érosion (Meur-Ferec et al , 2003, 2008Hénaff et Philippe (dir. ), 2014 ;Nichols et al 2019). Notre approche se nourrit bien sûr des travaux précédents, en particulier de ceux de D'Ercole (1994), qui définit la vulnérabilité des sociétés à travers leur capacité de réponse à des crises potentielles, capacité qui dépend de facteurs conjoncturels (l'aléa) et structurels (contexte social, économique, culturel, fonctionnel, institutionnel).…”
Section: La Vulnérabilité Systémique Interdisciplinaire Et Intersectorielleunclassified
“…The scale and frequency of these impacts, enhanced by a changing climate, requires a coordinated effort to prioritise, plan, and implement adaptation measures. Horizon scanning and collaborative priority setting exercises have been widely used to identify emerging issues and priorities in science, and to determine their relative importance from a researcher and practitioner perspective (e.g., Sutherland et al, 2011;Rudd and Lawton, 2013;Rudd, 2014;Nichols et al, 2019;Wisz et al, 2020). Within the discipline areas of marine and coastal science, several studies have been undertaken that have identified priority research questions and topics.…”
Section: Introductionmentioning
confidence: 99%